Determination of bandgaps of photoactive materials in perovskite solar cells at high temperatures by in-situ temperature-dependent resistance measurement - 朱浩 赵祖斌 曹焕奇 于昊 李今朝 陈晓敏 董素娟 杨利营 印寿根 (Optoelectronics letters, 2016)
Normally, it is difficult to directly measure the bandgaps of perovskite based on methylammonium（MA） or formamidinium（FA） at high temperatures due to material decomposition. We prevent the decomposition by keeping the synthesized perovskite films（MAPbI_3 and MAPbI_3） in organic iodide vapors, then measure the in-situ resistance of the films at varied temperatures, and further evaluate the bandgaps of these two materials. The evaluated bandgaps are consistent with the results from ultraviolet-visible（UV-vis） absorption spectrum. The bandgap of MAPbI_3 decreases with temperature above 95 ℃, whereas that of FAPbI_3 first increases with temperature from 95 ℃ to 107 ℃ and then decreases with temperature above 107 ℃.